THE ANALYSIS OF LESSON PLAN BASED ON SYNTAX AND CONTENT PROBLEMS IN ACCORDANCE WITH RULE MODEL OF PROBLEM BASED LEARNING - Agustina, Kristia; Kristiyanto, Wahyu Hari; Noviandini, Diane (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
This study aims to describe the results of the study of the implementation of Problem Based Learning model that has been done on previous research on the syntax, teacher behavior and the content of problems in Teaching and Learning Activities (KBM), especially in the field of Physics study, in terms of the Lesson Plans Program (RPP) and Student Worksheets (LKS) that have been made to the main literature. This research is a qualitative research with the descriptive approach on 7 samples RPP and 7 LKS. The results showed that the content of the problems did not match the PBL and the teacher behaviour on some samples in stage I (Organizing Students to Problem) and stage III (Assisting Self-Inquiry and Group) did not match the PBL syntax. The conclusion of this research is from the analysis of PBL model implementation that has been done in previous studies on the syntax, teacher behavior and the content of the problems in 7 samples of RPP and LKS shows that the teacher behavior that exist in the RPP there are some that are not in accordance with PBL syntax and the contents of the problems given to the students either written on the RPP or LKS mostly not actual because some of it is a matter of memorization that does not require creative thinking, mathematical calculations and problems looking for relationships between variables through experiments. Suggestion from this research that is in use of PBL model for making RPP and LKS in KBM need to refer five stages in PBL and problem has given to the student in PBL learning model should problem actual and require creative thinking and written clearly and completely in RPP and LKS.